Determinants of COVID-19 self-protection behavior of Thai people: a cross-sectional survey - Benjawee Srithanissorn; Kritsana Yonphet; Daranee Chiewchantanakit; Witoo Dilokthornsakul; Piyameth Dilokthornsakul (Faculty of Pharmacy, Mahidol University, 2022)
Background: Coronavirus disease 2019 (COVID-19) pandemic is a critical situation since 2020. Its outbreak occurs across the world. A national policy is to promote self-protection behavior including hand wash, wearing mask, and physical distancing. However, evidence on determinants of the behavior in Thai people is limited. This study aimed to identify determinants of COVID-19 self-protection behavior in Thai people. Design and Method: A cross-sectional survey was undertaken in January 2021. An online questionnaire was developed under the Health Belief Model (HBM). Participants who often or always behave COVID-19 self-protection was considered as proper self-protection behavior. Data was collected through social medias. Results: A total of 408 participants was included. Of those, 92 participants (22.5%) were male with the average age of 32.3?11.5 years. A total of 158 participants (38.7%) has proper self-protection behavior. Based on HBM, perceived threat [odds ratio (OR)=1.40, 95%CI 1.01-1.92], perceived barriers (OR=0.51, 95%CI; 0.36-0.71), and perceived self-efficacy (OR=6.77, 95%CI; 3.60-12.72) were significantly associated with self-protection behavior. Conclusion: One-third of participants have proper COVID-19 self-protection behavior. Perceived self-efficacy is the strongest determinant of COVID-19 self-protection behavior followed by perceived threat and perceived barriers.